SISTEM PROTEKSI GENERATOR TURBIN UAP (Studi Kasus: Pabrik Gula Camming) - Amin, Nurhani (MEKTEK, 2012)
This study aims to determine the extent of the protection system reliability steam turbine generator at Camming Sugar Factory in Bone regency against short circuit. Generator protection system reliability at Camming Sugar Factory in 1996 to 2003 reliability configuration is 1. In 2004 to 2007, the series reliability configuration is 0.9994, reliability parallel configuration is 1.0 and backup configuration is 0.9995. In 2008 to 2011, the series and parallel configurations reliability is 1, while the backup configuration is 0.9998. In 2012, the series reliability configuration are 0.9998, parallel eliability,configuration isÂ 0.0007 and backup configuration reliability is 1. This shows that the generator protection system reliability at Camming Sugar Factory classified very well.